Democracy, Resistance, and the Practice of Literature: Introduction - Arka Chattopadhyay; Sourit Bhattacharya (Sanglap: Journal of Literary and Cultural Inquiry, 2015)
Recent world politics has witnessed the rise of a certain style of authoritarianism. It can be roughly characterized with a cult of masculine leadership, a popular rhetoric of foreign investment and development, and a phobia of the illegal immigrant made into an ethical obligation. These contradictory forms of politics – the paean to multinational corporations, free trade, and the ‘bloc’-ing of power and the simultaneous mobilization of hyper-nationalism in the form of censoring books and throttling subversive aesthetic practices – characterize the conception and practice of what may be called “authoritarian democracy.” Considering the democratically elected basis of this authoritarianism, it becomes all the more important to ask if democracy paves the way for it. In that case, where do we locate democracy today? Is it right to say that the real democratic space unfolds itself in people’s movements and not in the electoral process? If this is the case, a radical conception of democracy would have to account for a shift of emphasis from the locus of governance to that of resistance and co-option. Historically speaking, democracy may not always be the means but it has been one of the ends for the various acts of resistance such as the working class, anti-colonial, nationalist, feminist, LGBT, or constitutional multiculturalism. In our sour and hungry times, when state aggression is overpowering the geographical marking (Russia’s in Ukraine or Israel’s in Palestine), or strangling the voice of internal resistance (North Eastern regions in India), not to mention religious fundamentalism, we need to rethink the old questions of democracy and resistance. With the ISIS, Boko Haram or the Taliban practice, we have seen how resistance itself can produce a dangerous authoritarianism which further complicates the relations between democracy, authoritarianism, and resistance. How do we historicize and ethically theorize resistance in relation to both democracy and an authoritarianism which borders on fascism?